1999
DOI: 10.1016/s0022-2275(20)32146-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phosphomevalonate kinase: chromosomal localization, regulation, and subcellular targeting

Abstract: Phosphomevalonate kinase catalyzes the conversion of mevalonate-5-phosphate to mevalonate-5-diphosphate and was originally believed to be a cytosolic enzyme. In this study we have localized the phosphomevalonate kinase gene to chromosome 1p13-1q22-23 and present a genomic map indicating that the gene spans more than 8.4 kb in the human genome. Furthermore, we show that message levels and enzyme activity of rat liver phosphomevalonate kinase are regulated in response to dietary sterol levels and that this regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The first indication of peroxisomal involvement in the biosynthesis of isoprenoids came from immunoelectron microscopy studies by Keller and coworkers (13), who localized HMG-CoA reductase (RED) in rat liver peroxisomes. Further studies have indicated that also mevalonate kinase (MVK) (14), phosphomevalonate kinase (PMK) (15), mevalonate pyrophosphate decarboxylase (MPD) (16), isopentenyl pyrophosphate isomerase (IPPI) (17), and farnesyl pyrophosphate synthase (FPPS) (18,19) are (partly) peroxisomal. Additional indirect support for a peroxisomal localization came from the observation that several enzymes involved in cholesterol biosynthesis contain consensus peroxisomal targeting sequences (8).…”
mentioning
confidence: 99%
“…The first indication of peroxisomal involvement in the biosynthesis of isoprenoids came from immunoelectron microscopy studies by Keller and coworkers (13), who localized HMG-CoA reductase (RED) in rat liver peroxisomes. Further studies have indicated that also mevalonate kinase (MVK) (14), phosphomevalonate kinase (PMK) (15), mevalonate pyrophosphate decarboxylase (MPD) (16), isopentenyl pyrophosphate isomerase (IPPI) (17), and farnesyl pyrophosphate synthase (FPPS) (18,19) are (partly) peroxisomal. Additional indirect support for a peroxisomal localization came from the observation that several enzymes involved in cholesterol biosynthesis contain consensus peroxisomal targeting sequences (8).…”
mentioning
confidence: 99%
“…As mentioned previously, studies have indicated that a number of the enzymes involved in these reactions are localized to the peroxisomes. However, mechanisms for targeting to peroxisomes have been demonstrated only for PMvK and IPP isomerase (26,27). In the current study we identify the peroxisomal targeting signals required for four other enzymes of the cholesterol biosynthetic pathway: AA-CoA thiolase, HMG-CoA synthase, MPPD, and FPP synthase.…”
Section: Discussionmentioning
confidence: 87%
“…The human sequence for these amino acids is NS(DVYA)QE. In contrast, a comparison of human and rodent sequences for AA-CoA thiolase (28,40), HMG-CoA synthase (41,42), MvK (43,44), PMvK (26,45), MPPD (46,47), and IPP isomerase (27,48) reveals that the peroxisomal targeting signals are conserved. Therefore, this apparent lack of sequence conservation of FPP synthase between mammalian species might indicate that the sequence is not a specific receptor-binding site.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations